Extension along the Australian-Pacific transpressional transform plate boundary near Macquarie Island - Daczko, NR; Wertz, KL; Mosher, S; Coffin, MF; Meckel, TA (Geochemistry, Geophysics, Geosystems, 2003)
The Australian-Pacific transform plate boundary fault zone along the Macquarie and McDougallsegments of the Macquarie Ridge Complex (MRC), south of New Zealand, is characterized by dominantlynormal faults and pull-apart basins, in apparent conflict with the regional transpressional tectonic setting.We propose that present-day curvature of the transform is inherited from a preexisting divergent plateboundary and that the overall extensional kinematics shown by faults along the main plate boundary traceand exposed on Macquarie Island result from local stresses related to right-lateral, right stepping, enechelon plate boundary faults and not to the current transpressional setting. Transpression along theAustralian-Pacific transform plate boundary has resulted in uplift along the ~1500 km long MacquarieRidge Complex. Macquarie Island, the only subaerial exposure of the complex, sits atop a ~5 km high,~50 km wide submarine ridge of oceanic crust and lies ~4.5 km east of the major active plate boundaryfault zone. Thus Macquarie Island and the surrounding seafloor provide a unique opportunity to study anactive oceanic transform fault using complementary marine geophysical and land-based geological data.Mapping of recent faults affecting the topography of Macquarie Island shows that the island is extensivelycut by high-angle normal faults forming pull-apart basins. Furthermore, evidence for reverse motion israre. Using marine geophysical data, including swath bathymetry, reflectivity, and seismic reflection data,collected along the Australian-Pacific plate boundary north and south of the island, we have defined a 5-15 km wide plate boundary zone. A series of right stepping en echelon faults, within this zone, liesalong the main plate boundary trace. At the right stepping fault terminations, elongate depressions (<=10 kmwide and 1.2 km deep) parallel the plate boundary, which we interpret as extensional relay zones or pullapartbasins. We propose that transpression is partitioned into en echelon strike-slip faults at ...